1990
DOI: 10.1038/icb.1990.51
|View full text |Cite
|
Sign up to set email alerts
|

Attempts to induce resistance in mice to Schistosoma japonicum and Schistosoma mansoni by exposure to crude schistosome antigens plus cloned glutathione‐S‐transferases

Abstract: Summary Several attempts have been made to induce resistance in mice to Schistosoma japonicum (Philippines) or Schistosoma mansoni by exposure to living male and/or female adult worms, their antigens or irradiated cercariae. No resistance was demonstrated in the following cases: re-exposure of mice to cercariae following praziquantel (PZQ) treatment of existing infection; re-exposure of mice following cyclosporin A (CsA) treatment at the time of first cerearial exposure; subcutaneous or intraperitoneal deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…These include Sm23 [39-45], integral membrane protein 25 [46], Sm14 [47,48], and 26 and 28 glutathione S-transferases [49-52]. …”
Section: Resultsmentioning
confidence: 99%
“…These include Sm23 [39-45], integral membrane protein 25 [46], Sm14 [47,48], and 26 and 28 glutathione S-transferases [49-52]. …”
Section: Resultsmentioning
confidence: 99%
“…However, despite exhibiting significantly elevated anti-worm responses, the mice remained fully susceptible to a secondary challenge infection. Mitchell and colleagues also investigated this phenomenon and found that immunizing mice with adult worm antigens in combination with PZQ treatment was still incapable of conferring protection from re-infection [39]. A large proportion of drug treated patients also remain highly susceptible to reinfection [30].…”
Section: Discussionmentioning
confidence: 99%
“…For many years, vaccine development approaches against human S. japonicum infection relied on testing S. japonicum homologues of S. mansoni vaccine candidates in the mouse model [16, 27, 28]. This approach has the advantage of rapid testing of antigens, however (1) some candidate vaccine antigens may be species–specific [17, 29]and (2) the concordance between the murine and human immune response against candidate schistosome vaccines is still unclear [30, 31].…”
Section: Discussionmentioning
confidence: 99%